"Just like talking to someone about like shit in your life and stuff, and they help you": Hopes and expectations for therapy among depressed adolescents. (2nd January 2016) - Midgley, Nick; Holmes, Joshua; Parkinson, Sally; Stapley, Emily; Eatough, Virginia; Target, Mary
Abstract: Objective: To explore hopes and expectations for therapy among a clinical population of depressed adolescents.Method: As part of a randomized clinical trial, 77 adolescents aged 11–17, with moderate to severe depression, were interviewed using a semi-structured interview schedule. The interviews were analysed qualitatively using framework analysis.Results: The findings are reported around five themes: "the difficulty of imagining what will happen in therapy, " "the 'talking cure, '" "the therapist as doctor, " "therapy as a relationship, " and "regaining the old self or developing new capacities."Conclusions: Differing expectations are likely to have implications for the way young people engage with treatment, and failure to identify these expectations may lead to a risk of treatment breakdown.